2017
DOI: 10.1111/jav.01334
|View full text |Cite
|
Sign up to set email alerts
|

How birds colonize cities: genetic evidence from a common waterbird, the Eurasian coot

Abstract: Much effort has been devoted to identify ecological and life‐history traits which facilitate urban colonization by wild avian species, but surprisingly little is known about the population‐level mechanisms of urbanization processes. In general, two different patterns of urban colonization have been proposed: 1) the model of independent colonization predicts that birds colonize cities independently in different geographical regions; 2) the model of leapfrog colonization assumes a single colonization event, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 67 publications
0
9
1
1
Order By: Relevance
“…An analysis of microsatellite data in the European kestrel Falco tinnunculus showed significant genetic differentiation (F ST = 0.063) between urban and rural sites lying at a distance of ca 90 km, while suburban pairs showed intermediate differentiation with both urban and rural conspecifics (Rutkowski et al 2006). Also, long-persistent urban populations of the Eurasian coot Fulica atra showed significant genetic divergence (F ST > 0.04) with nearby rural populations located 20-35 km from city borders, although a newly established urban population was more genetically similar to the population from adjacent wildland (Minias et al 2017). Similar patterns have been observed in passerine species.…”
Section: Discussionmentioning
confidence: 95%
“…An analysis of microsatellite data in the European kestrel Falco tinnunculus showed significant genetic differentiation (F ST = 0.063) between urban and rural sites lying at a distance of ca 90 km, while suburban pairs showed intermediate differentiation with both urban and rural conspecifics (Rutkowski et al 2006). Also, long-persistent urban populations of the Eurasian coot Fulica atra showed significant genetic divergence (F ST > 0.04) with nearby rural populations located 20-35 km from city borders, although a newly established urban population was more genetically similar to the population from adjacent wildland (Minias et al 2017). Similar patterns have been observed in passerine species.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, a large behavioural divergence between the recently established urban population in Łódź and an adjacent rural population indicates that these processes are very likely to be in operation. Our recent study of microsatellite divergence between several urban and rural coot populations from Poland suggested that Łódź was colonized by rural individuals rather than by birds originating from other urban populations, providing support for an independent model of colonization (Minias et al 2017). This means that coots which colonized the city of Łódź within the last 15 years were either behaviourally and physiologically pre-adapted to urban life (phenotype sorting) or were extremely plastic in their behaviour.…”
Section: Discussionmentioning
confidence: 90%
“…Expression of the following behavioural characters was assessed: aggression at the nest, exploitation of humanderived food resources, boldness towards humans during foraging, and stress responsiveness. In the previous work, we used population genetic methods to show that the new urban coot population from Łódź has been established via an influx of individuals from the nearby rural populations (Minias et al 2017). Thus, here we hypothesized that any behavioural differences between coots from Łódź and adjacent wildland should be interpreted as an effect of phenotype sorting or phenotypic plasticity.…”
Section: Behavioural Observationsmentioning
confidence: 99%
“…The presence of such relationship in the new urban population may suggest that consistency in habitat selection across the entire annual cycle is the result of behavioral plasticity or NHPI rather than the genetic background. The analysis of microsatellite variation indicated that coot population from Łódź was genetically more similar to neighboring semi- and non-urban populations than to old urban populations from Poland 62 . Łódź was colonized quite recently (beginning of twenty-first century) probably through an influx of individuals from the surrounding wildland (model of independent urban colonization) and microevolutionary adaptations related to a novel urban environment are unlikely to be fixed at the genetic level in such a short period of time since the colonization 62 .…”
Section: Discussionmentioning
confidence: 91%